PENGEMBANGAN METODE CITRA DIGITAL BERBASIS APLIKASI ANDROID UNTUK ANALISIS ION LOGAM Cr(VI) - Marti Hitsmi; Mochamad Lutfi Firdaus; Nurhamidah Nurhamidah (ALOTROP, 2020)
The presence of heavy metals in the environment can be a serious problem because it is harmful to human health. One of the heavy metal ions that pollute the environment is the Cr6+ metal ion. The usual tool used to analyze metal ions is Cr6+ is the Atomic Absorption Spectrometry (AAS) and Inductively Couple Plasma (ICP) which are very expensive and require trained personnel. The purpose of this study was to design a simple detector for Cr6+ metal ions as an alternative to conventional methods using AAS and ICP. The detection tool was developed using the android-based digital image method with SLR data analysis techniques obtained from the reaction of the metal ion complex Cr6 + with the compound dhypenilcarbazida (DPC). The parameters of the tool measured were accuracy, selectivity and sensitivity with the reaction of DPC compounds as complexes. The comparison level of this method is the complex method with DPC using a UV-Vis spectrophotometer. This research was carried out in the Chemistry Laboratory FKIP UNIB in November 2018 until March 2019. The implementation of tool parameters was tested to samples of aquatic environments in Bengkulu City, namely PDAM Kota Bengkulu water, tap water of FKIP UNIB Dean, Lake UNIB water, Sungai Hitam water and water Pantai Panjang. The results showed that the detection of Cr6+ metal ions made by the android-based digital image method had better accuracy, selectivity and sensitivity than conventional methods. The DPC is selective for Cr6 + metal ions with a change in color from clear to violet, at a wavelength of 540 nm. Accuracy was checked using a UV-Vis spectrophotometer with 99% accurate results. After that, test sensitivity to Cr6 + metal ions. using the android application method generates a Limit of Detection (LOD) of 6.7 ppb. The detector that was developed was applied to water samples in the city of Bengkulu, it turned out that all of the water samples showed that the levels of Cr6+ metal ions were still below the threshold determined by the Minister of Health Regulation, so it was still safe to use in everyday life.